TINJAUAN YURIDIS PEMBEBASAN NARAPIDANA SEBAGAI UPAYA PENANGGULANGAN COVID – 19 DI INDONESIA - Basri, Dimas Hasan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Several years ago Indonesia was shaken by a virus that claimed many victims, namely the covid - 19 virus, where many of the perpetrators of these crimes were carried out by ex-convicts, the release of these convicts was through assimilation by the ministry of law and human rights according to government directives, the purpose of releasing these convicts was to provide fresh air in carrying out a new life but what happened was the other way around, with the presence of the virus making ex-convicts commit crimes again to support their needs, the purpose of the authors to discuss this research is to find out what the principles of releasing ex-convicts during the Covid-19 pandemic are. and what are the legal consequences if the state does not release ex-convicts during the coid-19 pandemic, the method used in this research is normative, namely studying through the literature by examining the rules contained in the legislation, the conclusion obtained is that there is a principle in the principle of the chief of police which reads: "Salus Populi Supreme Lex Esto" in the sense of people's safety, is a reference for the release of convicts